EVALUATION INDEX STUDY ON DYNAMIC PERFORMANCE OF PARALLEL MECHANISM - LU KaiJiang; SHI JunPing; SHI GeMeng (Jixie qiangdu)
Used the theory of a vector norm and matrix norm,derived the analytical relationship of the relative variation quantity between the moving platform speed or acceleration and active joint driving force or torque of mechanism,proposed the evaluation index to quantify the velocity and acceleration performance,approaches respectively the Jacobi matrix and inertia matrix singularity locus in the work space,two singular locus determines the mechanism workspace boundary,the public parts of them can be used as a working space with excellent dynamic performance. Analyzed the coupling effect of the active joint velocity and acceleration. Proposed the evaluation metrics of the coupling degree between the active joints. Combined with the example,analyzed the coupling between the mechanism velocity and acceleration performance and active joints.